Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging